2001
DOI: 10.1094/pdis.2001.85.9.1032a
|View full text |Cite
|
Sign up to set email alerts
|

First Report of Aflatoxin in Dried Yam Chips in Benin

Abstract: Dried yam (Dioscorea spp.) chips are widely consumed in Bénin but are often attacked by molds. Invasion of food by Aspergillus flavus may lead to aflatoxin contamination. We report here the result of a survey on the sanitary quality of dried yam chips in Bénin. During July and August 2000, 50 dried yam chips samples were collected from different points in the marketing chain; 10 samples were collected from each of 5 stages: producers, wholesalers, retailers, dried yam-based food sellers and consumers. Aflatoxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 0 publications
1
10
1
Order By: Relevance
“…The AF presence is in agreement with previous surveys by Bankole and Adebanjo (2003), Bankole and Mabekoje (2004), and Jimoh and Kolapo (2008), who reported occurrence of AFs in yam chips in Nigeria, and by Bassa et al (2001) and Mestres et al (2004) who reported AFs in yam chips in Benin Republic.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The AF presence is in agreement with previous surveys by Bankole and Adebanjo (2003), Bankole and Mabekoje (2004), and Jimoh and Kolapo (2008), who reported occurrence of AFs in yam chips in Nigeria, and by Bassa et al (2001) and Mestres et al (2004) who reported AFs in yam chips in Benin Republic.…”
Section: Discussionsupporting
confidence: 92%
“…Jimoh and Kolapo (2008) also detected aflatoxins B 1 and G 1 in yam chips from Ibadan, Oyo state, Nigeria with mean concentrations of 14 and 17 mg kg À1 respectively. The presence of AFs has also been reported in yam chips from Benin Republic (Bassa et al, 2001;Mestres et al, 2004).…”
Section: Introductionmentioning
confidence: 70%
“…This is a common traditional method employed in Benin during the dry season (OctobereApril), especially in the Central and Northern regions of the country (Gnonlonfin et al, 2008). However the chips are still subject to attack by fungi such as Aspergillus, Fusarium and Penicillum (Bassa, Mestre, Hell, Vervia, & Cardwell, 2001;Gnonlonfin et al, 2008;Wareing et al, 2001). Fungal contamination can lead to mycotoxin production e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Aflatoxins have been reportedly detected in among others a wide range of spices including black pepper, ginger, red paprika and cumin as reviewed by McKee (1995), in dried fruits from Yemen (Alghalibi & Shater, 2004), in diseased fresh tomato (Lycopersicon esculentum Mill) from Sokoto, Nigeria (Muhammad, Shedu, & Amusa, 2004), and in shelled melon seeds from Nigeria (Bankole, Ogunsanwo, Osho, & Adewuyi, 2006). Bassa et al (2001) showed that Aspergillus colonized yam chips and they found that 98% of samples of yam chips were contaminated with aflatoxins with levels ranging from 2.2 to 220 mg/kg. A recent study conducted in Nigeria similarly reported the contamination of locally dried yam chips called elubo isu with aflatoxin B 1 (Bankole & Mabekoje, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Higher prevalence and contents of AF are observed in yam based products than in cassava products. Apart from the 100% frequency (Table 1) shown in Yam chips from Benin (Bassa et al 2009), 23% of the 107 samples analyzed by Mestres et al (2004) from the same country had AF levels over the 15 μg/kg CODEX standard value for total AF. AFB 1 and G 1 were detected in yam chips from Nigeria at levels ranging from 5-27µg/kg (Jimoh and Kolapo, 2008).…”
Section: Roots and Tubersmentioning
confidence: 97%